臺灣高科技新創事業於新興產業之策略研究 - 林士平 (My University, 2014)
近年來，新創事業對於發展新興產業的重要性日益受到學者們的關注。在發達國家如美國與英國， 新創事業愈來愈被視為是創新的重要來源以及經濟成長的引擎。在這些國家，新創企業對維持國家 競爭力扮演日益重要的作用。 像其他發展中國家一樣，台灣也在朝向一個以知識為基礎的知識經濟，從資本密集和生產為主的經 濟過渡到一個以科技為基礎，以服務為導向的混合經濟模式。近年來政府推出許多新舉措，以促進 新科技產業的興起，以及鼓勵創新的新創公司尋求競爭機會。 然而，儘管創業公司的重要性，究研初創企業的運營策略的出現和演進的研究，特別是新興產業的 新創企業卻相當缺乏。現有與策略相關的研究多著重在研究現有企業的策略。因此，現有文獻相當 缺乏能夠協助新創事業設計、啟動與管理營運策略的架構與工具。本研究的目的在於解決這些問題。 本研究調查台灣以科技為本的新創公司的策略之出現和演進，著重於新興產業的新創事業，目的是 制定一個策略制定框架，以支持這些企業的策略發展。 本研究採用解釋性方法，並採用定性的多個案的方法。個案將由台灣主要的科學園區、孵化中心和 加速器中選擇。資料蒐集包括使用可視化工具，如策略地圖以及深入了解公司的多方訪談，輔以其 他資料來源。在資料分析時則採取個案內與跨個案的分析法。 這項研究不僅能支持政策制定者設計能夠有效地促進和鼓勵創業活動的措施，也為從業者提供策略 發展的支持；它也能推動科技創業和經營策略領域的理論發展。

The importance of technology-based start-up companies in emerging industries have been steadily growing for years. In developed nation such as the United States and the UK, start-up companies are increasingly recognized as a key source of innovation and an engine of economic growth. In these countries, technology-based start-ups are playing an increasingly vital role for sustaining national competitiveness. Like many other developing nations aspiring to becoming a knowledge-based economy, Taiwan is seeing a transition from a capital-intensive and production-based economy to a hybrid of technology-based and service-oriented economy. The recent years have seen the government launching fresh initiatives to facilitate the emergence of new technology-based industries as well as to encourage innovative start-up companies to pursue competitive opportunities. However, despite the importance of start-up companies, little study has been found investigating how operations strategy emerges and evolves in start-ups, particularly those in emerging industries. Existing body of work concentrate mainly on studying strategy in established firms. Consequently, there is little collective knowledge about tools and frameworks that could support new firms design, initiate and manage their operations activities in their risky pursuit of entrepreneurial opportunities. This research addresses these issues. This research investigates the emergence and evolution of operations strategy in Taiwanese technology-based start-ups, focusing on those in emerging industries. It aims to develop strategy formulation frameworks that support strategy development in these companies. This research adopts an interpretative approach and uses qualitative multiple-case method. Cases will be selected from leading Taiwanese science parks, incubation centers and accelerators. Data collection will involve multiple interviews using visualization tools with multiple informants in each company. This will be supplemented by other data sources. Within-case and cross-case analysis methods will be used for data analysis. This research is significant not only for policy makers to design measures that could effectively promote and encourage entrepreneurial activities, but also for practitioners as a support for strategy development. It also advances theory development in the fields of technology entrepreneurship and operations strategy.
Strategy for Taiwanese High-Technology Start-Up Companies in Emerging Industries
Keywords: 臺灣; 高科技新創事業; 新興產業; 策略; 企業形成; 生產策略; 技術商品化; Taiwan; high-tech start-ups; emerging industries; strategy; business formation; operations strategy; technology commercialization